Pertunjukan Sholawat Rodad Sebagai Media Dakwah - Lina Amiliya (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2022)
Sholawat is worship that is light in its implementation but has great rewards, therefore it will be effective and efficient if sholawat is used as a medium for preaching. One of them is sholawat Rodad, because sholawat Rodad has its own uniqueness compared to other prayers. The purpose of this study is to explain how sholawat Rodad as a medium of da'wah. To obtain the results of this study the authors used qualitative methods with observation and interviews as data collection techniques. The results of this study state that every movement played by dancers has the meaning of da'wah, namely how a Muslim can maintain hablum minallah and hablum minannas so that the realization of a more prosperous life in the world and in the hereafter.